The Landa Vizcarra brothers - Valcárcel Salas, Gustavo (2021)
The brothers Tomás and Bernardo Landa initiated as defenders of the royalist cause, afterwards they militated in the fights for the independence and played an outstanding role in the campaigns of 1821 and 1823. Tomás was San Martín's secret emissary and one of his most active informants, he was awarded the Orden del Sol. Bernardo was subdelegated governor of Moquegua; he joined Miller in 1821, becoming his most effective collaborator in the brilliant southern campaign. After returning to Moquegua to prepare the campaign to puertos Intermedios, he was captured and shot in 1822.